Regulation of the expression and positioning of chemotaxis and motor proteins in Rhodobacter sphaeroides - Wilkinson, D; David Wilkinson (2010)
Bacteria achieve directed motion through their environments by integrating propulsion with chemical detection in the process of chemotaxis. Central to this process are the macromolecular protein structures of the flagellar motor and the chemoreceptor arrays, which are responsible for motility and chemical sensing, respectively. These protein complexes localise to different discrete subcellular positions in different bacterial species, and their correct subcellular localisation is often essential to their function. In the monotrichous α‐proteobacterium Rhodobacter sphaeroides, the flagellum is subpolar and two distinct sets of chemotaxis proteins localise to discrete polar and cytoplasmic positions within the cell. In this study, the development of software for the analysis of fluorescent microscopy images allowed cellular morphologies and the localisation and distribution of the chemoreceptor arrays of R.sphaeroides to be characterised in detail, showing that protein partitioning at cell division results in an asymmetric separation of both cytoplasmic and membrane‐bound protein components between daughter cells. The design of a fluorescence‐based assay for the analysis of gene expression assisted in demonstrating that expression of both the chemotaxis and motor genes of R.sphaeroides is regulated by the sigma factor, FliA, and its inhibitor, FlgM. FliA was then used to achieve varying expression of the chemotaxis genes, and the concentration dependence of array clustering was explored in microscopy images, revealing important differences between cluster formation in R.sphaeroides and other species.,/p> Additionally, FliA was identified as a regulator of flagellar number in R.sphaeroides, controlling a negative feedback‐loop in the hierarchy of flagellar assembly that represses flagellar formation upon secretion of FlgM. The complex regulatory pathway controlling R.sphaeroides flagellar assembly is the first identified system where completion of a single flagellum directly inhibits the production of a second, a mechanism that may be important to many monotrichous bacterial species.